2021
DOI: 10.3390/md19010019
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Antibiofilm Activity of Elasnin against Marine Biofilms and Its Application in the Marine Antifouling Coatings

Abstract: Biofilms are surface-attached multicellular communities that play critical roles in inducing biofouling and biocorrosion in the marine environment. Given the serious economic losses and problems caused by biofouling and biocorrosion, effective biofilm control strategies are highly sought after. In a screening program of antibiofilm compounds against marine biofilms, we discovered the potent biofilm inhibitory activity of elasnin. Elasnin effectively inhibited the biofilm formation of seven strains of bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Elasnin was recently reported to exhibit antibiofilm activity against multiple Gram-positive and -negative bacteria and can be used as a coating agent in marine environments ( 5 ). Furthermore, a mechanistic study of its antibiofilm activity in MRSA has been recently performed, revealing that elasnin suppressed the production of virulence factors which resulted in a lower expression of extracellular EPS, cell wall, and membrane components, as well as peptidoglycan hydrolases, which are important for cell wall formation during cell division ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elasnin was recently reported to exhibit antibiofilm activity against multiple Gram-positive and -negative bacteria and can be used as a coating agent in marine environments ( 5 ). Furthermore, a mechanistic study of its antibiofilm activity in MRSA has been recently performed, revealing that elasnin suppressed the production of virulence factors which resulted in a lower expression of extracellular EPS, cell wall, and membrane components, as well as peptidoglycan hydrolases, which are important for cell wall formation during cell division ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elasnin was prepared according to a previously described protocol ( 5 ). Briefly, stock cultures of Streptomyces mobaraensis DSM 40847 were inoculated into AM4 medium (soybean powder [20 g/L], bacteriological peptone [2 g/L], glucose [20 g/L], soluble starch [5 g/L], yeast extract [2 g/L], NaCl [4 g/L], K 2 HPO 4 [0.5 g/L], MgSO 4 ·7H 2 O [0.5 g/L], CaCO 3 [2 g/L] [pH 7.8]) and incubated at 30°C for 5 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the AF natural products project screening, the polyketide compound elasnin (51) highly produced by Streptomyces mobaraensis DSM 40847 exhibited strong biofilm inhibition activity against four marine bacterial Gram-positive strains Staphylococcus aureus B04, S. hominis N32, S. arlettae OM, and Microbacterium esteraromaticum N22 with MBIC 90 and MBIC 50 ranged from 2.5 to 5 µg/mL and 1.25 to 5 µg/mL, whereas three gram-positive strains Idiomarina sediminum N28, Pseudoalteromonas sp. L001, and Escherichia coli N57 with MBIC 90 of 5 to 10 µg/mL and MBIC 50 of 1.25 to 10 µg/mL, respectively [43]. The larval settlement of Balanus amphitrite was also effectively inhibited at concentrations above 12.5 µg/mL after 24 h exposure.…”
Section: Glycolipids Benzenoids Flavonoids Polyketides and Enzymesmentioning
confidence: 95%
“…Several studies have suggested that elasnin could be used to treat chronic obstructive lung disease caused by leukocyte elastase that damages the lung tissue ( 3 , 4 ). Recently, the antibiofilm activity of elasnin was explored, and it was reported that elasnin inhibited biofilm formation of multiple species in the marine environment, including some Gram-positive bacteria such as Staphylococcus aureus ( 5 , 6 ). Further investigation showed that elasnin did not only inhibit biofilm formation, but also effectively eradicated the biofilms of methicillin-resistant Staphylococcus aureus (MRSA) through the repression of the virulence regulon and interference of the cell division process (i.e., by suppressing the production of newly synthesized extracellular polymeric substance [EPS], cell wall and membrane components, and peptidoglycan hydrolases that are needed to finish cell wall formation) ( 7 ).…”
Section: Introductionmentioning
confidence: 99%